2020
DOI: 10.1111/cen.14392
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in acromegaly at diagnosis: A nationwide cohort study and meta‐analysis of the literature

Abstract: Objective Data on sex differences in acromegaly at the time of diagnosis vary considerably between studies. Design A nationwide cohort study including all incident cases of acromegaly (1978–2010, n = 596) and a meta‐analysis on sex differences in active acromegaly (40 studies) were performed. Method Sex‐dependent differences in prevalence, age at diagnosis, diagnostic delay, pituitary adenoma size, insulin‐like growth factor 1 (IGF‐I) and growth hormone (GH) concentrations were estimated. Results The cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 63 publications
1
32
1
7
Order By: Relevance
“…Female patients have more prolonged diagnostic delays compared to males [6]. While over the years there have been improvements in the diagnostic procedures for acromegaly, including the availability of serum IGF-1 measurement and more sensitive GH assays, the diagnostic delay and the age at diagnosis have not changed, and that is mostly secondary to the insidious onset of the clinical features, overlap of the signs and symptoms with other common conditions, and lack of disease awareness among other medical specialists [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Female patients have more prolonged diagnostic delays compared to males [6]. While over the years there have been improvements in the diagnostic procedures for acromegaly, including the availability of serum IGF-1 measurement and more sensitive GH assays, the diagnostic delay and the age at diagnosis have not changed, and that is mostly secondary to the insidious onset of the clinical features, overlap of the signs and symptoms with other common conditions, and lack of disease awareness among other medical specialists [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in some studies, a balanced sex distribution or male predominance has also been observed [10,14,21,22]. In recently published data from a Denmark-based nationwide cohort study including all incident cases of acromegaly from 1978 to 2010, a balanced sex distribution and comparable age at the time of diagnosis were identified [10]. However, in that study, sex distribution was associated with the calendar year, when the acromegaly was confirmed (from initial female predominance to more even sex balance).…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon is observed in autoimmune diseases as well as in pituitary tumorigenesis. Some studies suggest the role of estrogens as a potential trigger, especially in prolactinomas [10,[18][19][20]. In most studies of acromegaly patients, females are slightly more frequently affected than males (1.24:1) [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations